Analisis Dan Pemodelan Proses Bisnis Event Pada Dinas Pemuda dan Olahraga Sumatera Utara - Triase, Triase; Ardhana, Muhammad Reza; Matanari, Hanif Kurniawan (Jurnal Ilmiah Sains dan Teknologi, 2024)
The North Sumatra Youth and Sports Service is one of the government agencies responsible for youth services, partnership services, sports services and supporting services as regulated by law in North Sumatra Province. Therefore, this research was conducted with the aim of modeling and mapping the business processes of the North Sumatra Youth and Sports Department in accordance with Minister of Youth and Sports Regulation. By using Business Process Model Notation (BPMN) for business process notation and flowcharts for notation in compiling SOP documents. This research begins with assessing SOP needs, planning and preparing business processes, developing business processes, then verifying the business processes created, compiling SOPs and carrying out SOP verification and SOP validation. The results of this research are in the form of an optimum and efficient event business process model, as well as recommendations for improvements that can be implemented by the Youth and Sports Department.